Polymer resin as well as preparation method and application thereof
By introducing triazine and sulfide structures into the optical resin material, a polymer resin with a high molar refractive index is solved, and the existing optical resin materials have low refractive index, complex process and prone to yellowing are achieved, and the effects of high refractive index, good light transmittance and thermal stability are achieved.
Patent Information
- Application Number
- CN202411934784.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-08
AI Technical Summary
The refractive index of existing optical resin materials is low, resulting in thicker thickness, high cost and poor light efficiency of the optical devices. At the same time, the synthesis process is complex, prone to yellowing, poor solubility and low molecular weight, which limits its application in the field of optical.
A polymeric resin containing triazine structure and sulfide structure is used. The monomer contains groups with high molar refractive index and rich hydrogen bond acceptors and donors. Through multiple hydrogen bonding, a dense stacking structure is formed, which increases the refractive index, and a polymeric resin with high molecular weight and good thermal stability is obtained through simplified synthesis technology.
The high refractive index (refractive index higher than 1.8), good light transmittance, thermal stability and yellowing resistance of polymer resin are achieved, reducing process difficulty and production costs, and improving light efficiency and processing convenience.
Smart Images

Figure CN119775560A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of optical materials, in particular to polymer resin and a preparation method and application thereof. Background Art
[0002] Optical materials are mainly divided into two categories: glass and resin, and are widely used in many fields such as display, lens, sensor, etc. Among them, optical resin materials are gaining more and more attention in the field of optical materials.
[0003] Existing optical resin materials, such as polycarbonate resin materials and resin materials formed by curing isocyanate-thiol, have a low refractive index of less than 1.7, resulting in thick optical devices made from them, high cost, and poor light efficiency. Other optical resin materials, such as modified polyphenylene sulfide, have complex synthesis processes, are prone to yellowing due to oxidation of the benzene ring, have poor solubility, and have low molecular weight, which limits the application of this material in the optical field. Summary of the invention
[0004] In view of this, the present invention proposes a polymer resin and a preparation method and application thereof, aiming to solve at least one of the aforementioned technical problems and achieve high refractive index, high molecular weight, good thermal stability and anti-yellowing properties of the polymer resin.
[0005] The polymer resin provided in the first aspect of the present invention has the following general structural formula as shown in Formula I:
[0006]
[0007] Wherein, the value of n is a positive integer between 1 and 10000; and R is an electron-rich group.
[0008] It can be seen from the above technical scheme that the polymer resin proposed in the first aspect of the present invention contains triazine structure and thioether structure in its monomer, and S has a high proportion in the whole molecule. S itself is a group with high molar refractive index, and the propagation speed of light slows down when passing through, which increases the refractive index. The resin not only contains abundant hydrogen bond acceptors including groups such as N in thioether structure and triazine structure, but also contains abundant hydrogen bond donors on the side chain groups. Multiple hydrogen bonds with different strengths can enhance the intermolecular forces between resins and achieve the effect of dense stacking, thereby further improving the refractive index, so that the whole molecule of the polymer resin has a higher refractive index. In addition, the atomic radius of S is large, and it is not easy to form a conjugated structure between groups and atoms, and between groups and groups, and the light absorption is weak; hydrogen bonds of different types and strengths in the molecule can also effectively avoid the formation of an ordered crystalline structure between monomers, and instead form an amorphous stacking structure, which effectively avoids light scattering and makes the polymer resin as a whole have good light transmittance. The polymer resin of the present invention has both hydrogen bond acceptors and hydrogen bond donors on the monomer, and has good solubility; the rigid structure of the triazine structure and the lower chain freedom in the polymer resin make the entire polymer resin have good thermal stability, lower shrinkage, and easy processing.
[0009] In some possible embodiments of the present invention, R is selected from any one of hydroxyl, amino, methoxy, and phenyl; and / or,
[0010] The polymer resin is selected from the group consisting of Any one of the compounds in .
[0011] In some possible embodiments of the present invention, the refractive index of the polymer resin is higher than 1.8.
[0012] The preparation method of the polymer resin provided in the second aspect of the present invention comprises the following steps: using sodium sulfide and a structural formula of 1:1 in a molar ratio The dichlorotriazine compound is used as a reactant, and is subjected to a constant temperature catalytic reaction with a solvent N-methylpyrrolidone for a period of time, and the product is cooled and cleaned to obtain a general formula of of polymer resin.
[0013] It can be seen from the above technical scheme that the preparation method of the polymer resin proposed in the second aspect of the present invention has few preparation steps and can realize the synthesis of the polymer resin with only one main reaction. The dichlorotriazine compound used contains both hydrogen bond acceptors and hydrogen bond donors, and becomes hydrogen bond acceptors and hydrogen bond donors in the polymer resin after polymerization. It is not necessary to modify the polymer resin to obtain molecules with hydrogen bond acceptors and hydrogen bond donors at the same time, which simplifies the synthesis process and reduces the process difficulty and production cost. The prepared polymer resin has high refractive index, good thermal stability, easy processing and good solubility.
[0014] In some possible embodiments of the present invention, the temperature of the isothermal reaction is 200°C to 270°C; the time of the isothermal reaction is 2h to 6h; and / or the catalyst used in the reaction includes at least one of lithium chloride, aluminum chloride, magnesium chloride, lithium acetate, lithium benzoate, lithium stearate and caprolactam; and / or the auxiliary agent used in the reaction includes at least one of sodium carbonate, sodium hydroxide, benzoate and phosphate; sodium sulfide and dichlorotriazine compound are protected by nitrogen atmosphere during the reaction; and / or the washing liquid used for cleaning is one or more of ethanol, potassium hydroxide solution, water and methanol.
[0015] In some possible embodiments of the present invention, the dichlorotriazine compound is one of 4,6-dichloro-1,3,5-triazine-2-amine, 2,4-dichloro-6-methoxy-1,3,5-triazine, and 2,4-dichloro-6-phenyl-1,3,5-triazine; when 4,6-dichloro-1,3,5-triazine-2-amine is used as a reactant, the final structure is When 2,4-dichloro-6-methoxy-1,3,5-triazine is used as the reaction
[0016] |
[0017] When the compound is finally obtained, the structural formula is When 2,4-dichloro-6-phenyl-1,3,5-triazine is used as the reactant, the final obtained structure is of polymer resin.
[0018] In some possible embodiments of the present invention, the method for preparing the polymer resin further comprises the following steps: using a The polymer resin is used as a reactant, dissolved in dichloromethane under an argon atmosphere, and a boron tribromide solution is added, stirred at 0°C for a first time, stirred at room temperature for a second time, and the dichloromethane is removed to leave the reaction solution. The reaction solution is dispersed with methanol and precipitated with water multiple times to obtain a precipitate with the structural formula: of polymer resin.
[0019] In some possible embodiments of the present invention, the first time is 20 minutes to 40 minutes, and the second time is 10 hours to 30 hours.
[0020] The optical waveguide structure provided in the third aspect of the present invention includes a substrate made of the polymer resin in the above examples; or includes a high-refractive film material made of the polymer resin in the above examples.
[0021] It can be seen from the above technical solutions that the optical waveguide structure proposed in the third aspect of the present invention, by using the aforementioned polymer resin to make the substrate or high-refractive film material, has the advantages brought by the polymer resin, high refractive index and good light transmittance, can effectively reduce thickness, reduce costs, and has certain yellowing resistance characteristics.
[0022] The optical device provided in the fourth aspect of the present invention includes the optical waveguide structure in the aforementioned example.
[0023] It can be seen from the above technical solutions that the optical device proposed in the fourth aspect of the present invention can reduce thickness, facilitate processing, and reduce costs, and light can propagate along a predetermined optical path and produce clear imaging.
[0024] It should be understood that the above general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosure of the embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained like these accompanying drawings without paying any creative work.
[0026] Figure 1 Schematic diagram of the chemical reaction principle of the polymer resin P1 proposed in Example 1 of the present invention;
[0027] Figure 2 Schematic diagram of the chemical reaction principle of the polymer resin P2 proposed in Example 2 of the present invention;
[0028] Figure 3 Schematic diagram of the chemical reaction principle of the polymer resin P3 proposed in Example 3 of the present invention;
[0029] Figure 4 It is a schematic diagram of the chemical reaction principle of demethylation of polymer resin P4 proposed in Example 4 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention.
[0031] In the absence of conflict, the following embodiments and features of the embodiments may be combined with each other.
[0032] Optical materials are mainly divided into two categories: glass and resin, and are widely used in many fields such as display, lens, sensor, etc. Among them, optical resin materials are gaining more and more attention in the field of optical materials due to their advantages such as low specific gravity, high impact toughness, rich structural design, and easy processing. The refractive index of optical resin materials is one of the important indicators reflecting the performance of its materials, and a higher refractive index can effectively improve the light efficiency. After being made into a light-transmitting material, it can also reduce the material thickness, reduce the weight, and improve the light efficiency.
[0033] However, the existing polycarbonate resin materials and the resin materials cured by polythiol and isocyanate have low refractive index; the existing hydroxyl-modified polyphenylene sulfide has a complex synthesis process, the benzene ring is easily yellowed due to oxidation, the solubility is poor, the molecular weight is low, and it is difficult to process.
[0034] Therefore, the present invention provides a polymer resin, which contains a triazine group with a high refractive index, a thioether group with a high refractive index and an electron-rich group, and exists in the form of a polymer. It not only has a high molecular weight, but also has hydrogen bond acceptors and hydrogen bond donors in the molecule. The entire molecule forms an amorphous stacking structure with a high refractive index.
[0035] The polymer resin provided in the embodiment of the present invention has the following general structural formula as shown in Formula I:
[0036]
[0037] Wherein, the value of n is a positive integer between 1 and 10000; and R is an electron-rich group.
[0038] Exemplarily, the value of n can be any integer between 1, 10, 20, 30, 50, 100, 200, 500, 700, 900, 1000, 2000, 5000, 7000, and 10000. By limiting the value of n to the above range, not only can a polymer resin with a moderate molecular weight be obtained, but also the entire polymer resin can be formed into an amorphous stacking structure, thereby improving the refractive index and light transmittance of the entire polymer resin. In some further embodiments, the value of n is any value in the range of 15 to 5000 and includes 15 and 5000.
[0039] As can be seen from the above technical solution, the polymer resin proposed by the present invention contains a triazine structure and a thioether structure in its monomer, and S has a high proportion in the entire molecule. S itself is a group with a high molar refractive index, and the propagation speed of light slows down when passing through, thereby increasing the refractive index of the entire polymer resin. The refractive index of the triazine structure is also higher than 1.5, providing a structural basis for the high refractive index of the entire polymer resin.
[0040] The resin contains not only abundant hydrogen bond acceptors including N groups in thioether structure and triazine structure, but also abundant hydrogen bond donors on the side chain groups. The multiple hydrogen bonds with different strengths can enhance the intermolecular forces between the resins and achieve the effect of dense stacking, thereby further improving the refractive index, making the entire molecule of the polymerized resin have a higher refractive index, which can reach above 1.8.
[0041] In addition, S has a large atomic radius, and it is not easy to form a conjugated structure between groups and atoms, and between groups, so the light absorption is weaker; hydrogen bonds of different types and strengths in the entire molecule can also effectively prevent the formation of an ordered crystalline structure between monomers, and instead form an amorphous stacking structure, which effectively avoids light scattering and makes the polymer resin as a whole have good light transmittance.
[0042] The chain structure of the monomer in the polymer resin of the present invention has hydrogen bond acceptors and hydrogen bond donors at the same time, and the introduction process does not require additional modification steps, and the processing is easy and the production cost is low; it can reduce or eliminate the phenomenon that the hydroxyl group added to the phenyl group forms an active site when polyphenylene sulfide is modified, and yellowing occurs in the later use; that is, compared with the modified polyphenylene sulfide in the prior art, which is easy to react under light, high temperature or oxygen in the later stage due to the high activity of the hydroxyl group, and then easily produces yellowing, the hydrogen bond acceptors and hydrogen bond donors of the present invention are embedded in the main chain of the molecule at the same time, and can form relatively strong hydrogen bonds with each other, which are not easy to be oxidized and therefore not easy to yellow. In addition, when the hydrogen bond acceptors and hydrogen bond donors exist together, the solubility of the entire molecule can also be improved.
[0043] The triazine structure of the present invention has a rigid structure and a lower chain freedom in the polymer resin, so that the entire polymer resin has good thermal stability, a lower shrinkage rate, good mechanical properties and is easy to process.
[0044] It can be understood that, compared with the low refractive index polycarbonate resin material and the resin material cured by polythiol and isocyanate in the prior art, the polymer resin of this embodiment has a refractive index higher than 1.8 and excellent light transmittance. Compared with the polyphenylene sulfide in the prior art that is prone to yellowing and has poor solubility, the polymer resin of the present invention has stable mechanical properties, is not prone to yellowing, and has good solubility.
[0045] In some embodiments of the present invention, R is selected from any one of hydroxyl, amino, methoxy, and phenyl, and correspondingly, the polymer resin is selected from the structural formula Any one of the compounds in .
[0046] The hydroxyl group, amine group, methoxy group, and phenyl group in these examples all contain abundant electrons, and NH, OH, and CH are all abundant hydrogen bond donors, so that the entire polymer resin molecule contains abundant hydrogen bond donors; the nitrogen atoms in the thioether and triazine structures, and the oxygen atoms with lone pairs of electrons on R, the nitrogen atoms with lone pairs of electrons, and the carbon atoms with lone pairs of electrons form abundant hydrogen bond acceptors. Then, when the hydrogen bond donors and hydrogen bond acceptors on different monomers in the polymer resin molecule are combined, hydrogen bonds with strong force are formed, which is beneficial for the entire molecule to form an amorphous dense stacking structure, thereby improving the refractive index of the polymer resin of the present invention.
[0047] In some embodiments of the present invention, the refractive index of the polymer resin is higher than 1.8, and the polymer resin of the present invention can be applied to optical waveguide structures, especially after being made into lenses, the lens thickness is small, the light efficiency is high, the processing cost is low, and the wearing experience is good.
[0048] Next, a method for preparing the polymer resin of the present invention will be described.
[0049] The method for preparing the polymer resin provided by the present invention comprises the following steps:
[0050] S10, using sodium sulfide with a molar ratio of 1:1 and a structural formula of The dichlorotriazine compound is used as a reactant, and a constant temperature catalytic reaction is carried out for a period of time together with a solvent N-methylpyrrolidone. The solvent N-methylpyrrolidone used in step S10 can not only dissolve sodium sulfide, the dichlorotriazine compound and the catalyst at the same time, making the reaction system more uniform, but also maintain a relatively stable state during the constant temperature reaction without thermal decomposition, thereby allowing the two reactants to fully react chemically at a certain temperature under the action of the catalyst.
[0051] In some embodiments, the temperature of the isothermal reaction is 200° C. to 270° C. For example, the temperature may be 200° C., 210° C., 220° C., 230° C., 240° C., 260° C., or 270° C., etc. Controlling the reaction temperature within the above range can increase the reaction rate of the two reactants, increase the activity of the catalyst, and thus increase the efficiency of the entire reaction, and help reduce the generation of by-products.
[0052] In some examples, the isothermal reaction time is 2 hours to 6 hours. For example, the isothermal reaction time is 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours or 6 hours. Controlling the isothermal reaction time within the above range can allow the two reactants to react fully and reduce residual reactants.
[0053] In some examples, the catalyst used in the reaction includes at least one of lithium chloride, aluminum chloride, magnesium chloride, lithium acetate, lithium benzoate, lithium stearate and caprolactam. These substances have strong nucleophilicity and can attack the C-Cl bond in the dichlorotriazine compound, reduce the activation energy required for the reaction, and thus enable the dichlorotriazine compound and sodium sulfide to react faster. When there are multiple catalysts, they can be in any proportion and can be selected according to actual needs.
[0054] In some examples, the auxiliary agent used in the reaction includes at least one of sodium carbonate, sodium hydroxide, benzoate and phosphate. These substances, as auxiliary agents, can enhance the nucleophilic attack performance of the catalyst on the reactant when combined with the catalyst, thereby accelerating the reaction process.
[0055] In some examples, sodium sulfide and dichlorotriazine compounds are protected by nitrogen atmosphere during the reaction. Nitrogen is relatively stable and can isolate oxygen and other gases from interfering with the reaction, reduce the generation of by-products, and improve the yield of the product.
[0056] S20, cooling and cleaning the product to obtain the general formula: Cooling down not only stabilizes the properties of the polymer resin, but also improves the safety of experimental operations.
[0057] In some examples, the washing liquid used for washing is one or more of ethanol, potassium hydroxide solution, water and methanol. Ethanol and methanol have good compatibility with water or organic reagents, so the solvent and inorganic solution attached to the reaction product can be quickly washed away to improve the purity of the reaction product. For example, in a specific example, ethanol, 5wt% potassium hydroxide solution, water and methanol can be used for washing respectively, so as to obtain a reaction product with higher purity.
[0058] In some examples, after the reaction product is washed, it is further post-processed by vacuum drying to remove volatile solvents and obtain a purer polymer resin.
[0059] As can be seen from the above technical scheme, the preparation method of the polymer resin proposed by the present invention has few preparation steps and can realize the synthesis of the polymer resin with only one main reaction. The dichlorotriazine compound used contains both hydrogen bond acceptors and hydrogen bond donors, and becomes hydrogen bond acceptors and hydrogen bond donors in the polymer resin after polymerization. It is not necessary to modify the polymer resin to obtain molecules with hydrogen bond acceptors and hydrogen bond donors at the same time, which simplifies the synthesis process and reduces the process difficulty and production cost. The prepared polymer resin has high refractive index, good thermal stability, easy processing and good solubility.
[0060] In some embodiments of the present invention, the dichlorotriazine compound is one of 4,6-dichloro-1,3,5-triazine-2-amine, 2,4-dichloro-6-methoxy-1,3,5-triazine, and 2,4-dichloro-6-phenyl-1,3,5-triazine.
[0061] When 4,6-dichloro-1,3,5-triazine-2-amine is used as a reactant, 4,6-dichloro-1,3,5-triazine-2-amine reacts with sodium sulfide to finally obtain a structural formula of of polymer resin.
[0062] When 2,4-dichloro-6-methoxy-1,3,5-triazine is used as a reactant, 2,4-dichloro-6-methoxy-1,3,5-triazine reacts with sodium sulfide to finally obtain a structural formula of of polymer resin.
[0063] When 2,4-dichloro-6-phenyl-1,3,5-triazine is used as a reactant, 2,4-dichloro-6-phenyl-1,3,5-triazine reacts with sodium sulfide to obtain a final product having the structural formula: of polymer resin.
[0064] In some other embodiments of the present invention, the method for preparing the polymer resin further comprises the following steps:
[0065] Step S30, using the structural formula The polymer resin is used as a reactant, dissolved in dichloromethane under an argon atmosphere, and a boron tribromide solution is added, stirred at 0°C for a first time, stirred at room temperature for a second time, and the dichloromethane is removed to leave the reaction solution. The reaction solution is dispersed with methanol and precipitated with water multiple times to obtain a precipitate with the structural formula: Then, in step S30, a series of demethylation reactions can be performed to obtain a polymer resin having a structural formula of The polymer resin is converted into the structural formula The polymer resin of the present invention is converted into -OH, and the refractive index of hydroxyl group is 1.695, which is higher than the refractive index of methoxy group 1.428, thereby helping to improve the overall refractive index of the polymer resin of the present invention. The dichloromethane and boron tribromide attached to the reaction product can be effectively removed by adding methanol for dispersion and water for precipitation multiple times, and a polymer resin with a hydroxyl group as R of higher purity can be gradually obtained.
[0066] In the present invention, the first time in step S30 is 20 min to 40 min, for example, 20 min, 30 min, 40 min, etc.; the second time in step S30 is 10 h to 30 h, for example, 10 h, 15 h, 20 h, 25 h or 30 h, etc. By reacting at 0 ° C for the first time, the reaction is fully carried out at a lower temperature, and the generation of by-products is avoided, thereby improving the safety of the reaction. By reacting at room temperature for the second time, the reaction conditions are easy to control and are conducive to the generation and separation of products.
[0067] In some examples, the dichloromethane taken out in step S30 can be removed by a rotary evaporator. Dichloromethane has good volatility and is easy to remove.
[0068] In some examples, after the precipitate is dispersed with methanol and washed with water, it is also vacuum dried to remove moisture, and finally a polymer resin in which R is a hydroxyl group is obtained.
[0069] Next, the optical waveguide structure of the present invention will be described.
[0070] The optical waveguide structure proposed in the present invention includes a substrate made of the polymer resin in the above examples; or includes a high-folding film material made of the polymer resin in the above examples.
[0071] As can be seen from the above technical solution, the optical waveguide structure proposed in the present invention, by using the aforementioned polymer resin to make the substrate or high-refractive film material, has the advantages brought by the polymer resin, high refractive index and good light transmittance, high light efficiency, can effectively reduce thickness, reduce costs, and has a certain yellowing resistance.
[0072] Next, the optical device of the present invention will be described.
[0073] The optical device proposed in the present invention includes the optical waveguide structure in the above example. The optical device can be an augmented reality device (AR device, Augmented Reality), a virtual reality device (VR device, Virtual Reality), a head-up display device (HUD, Head Up Display), etc.
[0074] As can be seen from the above technical solutions, the optical device proposed by the present invention can reduce thickness, facilitate processing, reduce costs, and light can propagate along a predetermined optical path with clear imaging. Especially when used in the field of AR glasses display, using the high refractive index polymer resin of the present invention as part of the optical waveguide structure can effectively improve light efficiency, reduce lens thickness, reduce costs, and obtain a good wearing experience.
[0075] The polymer resin and the preparation method of the polymer resin of the present invention are described below in conjunction with specific embodiments.
[0076] Example 1
[0077] The structural formula of the polymer resin P1 in this embodiment is: Where n is 20.
[0078] Please refer to Figure 1 The preparation method of the polymer resin P1 wherein R is an amine group comprises the following steps:
[0079] 70 mL of NMP and 3.77 g of sodium sulfide were added to the autoclave from the feed port. The temperature was raised to 140 ° C, dehydrated for half an hour, and 0.5 g of lithium chloride and sodium carbonate were added, and about 8.068 g of 4,6-dichloro-1,3,5-triazine-2-amine was added, with the molar ratio of sodium sulfide to 4,6-dichloro-1,3,5-triazine-2-amine being 1:1. The reactor was sealed, and after nitrogen replaced the air in the reactor, the pressure was raised to 220 ° C, and the reaction was kept at a constant temperature for 2.5 hours, and then the heating was stopped and the temperature was slowly lowered to form a reaction solution. The reaction solution was precipitated by adding water, and the solid was collected by filtration. The solid was then washed with ethanol and 5 wt% potassium hydroxide solution, water and methanol, respectively, and vacuum dried to obtain the polymer resin P1.
[0080] Example 2
[0081] The structural formula of the polymer resin P2 in this embodiment is: Where n is 30.
[0082] Please refer to Figure 2 The preparation method of the polymer resin P2 in which R is methoxy is as follows:
[0083] 70 mL of NMP and 3.77 g of sodium sulfide were added to the autoclave from the feed port. The temperature was raised to 140 ° C, dehydrated for half an hour, and 0.5 g of lithium chloride and sodium carbonate were added, and about 8.695 g of 2,4-dichloro-6-methoxy-1,3,5-triazine was added, with the molar ratio of sodium sulfide to 2,4-dichloro-6-methoxy-1,3,5-triazine being 1:1. The reactor was sealed, and after nitrogen replaced the air in the reactor, the pressure was raised to 220 ° C, and the reaction was kept at a constant temperature for 3 hours, and then the heating was stopped and the temperature was slowly lowered to form a reaction solution. The reaction solution was precipitated by adding water, and the solid was collected by filtration. The solid was then washed with ethanol and 5wt% potassium hydroxide solution, water and methanol, respectively, and vacuum dried to obtain the polymer resin P2.
[0084] Example 3
[0085] The structural formula of the polymer resin P3 in this embodiment is: Where n is 40.
[0086] Please refer to Figure 3 The preparation method of the polymer resin P3 in which R is phenyl is as follows:
[0087] 70 mL of NMP and 3.77 g of sodium sulfide were added to the autoclave from the feed port. The temperature was raised to 140 ° C, dehydrated for half an hour, and 0.5 g of lithium chloride and sodium carbonate were added, and about 10.921 g of 2,4-dichloro-6-phenyl-1,3,5-triazine was added, with the molar ratio of sodium sulfide to 2,4-dichloro-6-phenyl-1,3,5-triazine being 1:1. The reactor was sealed, and after nitrogen replaced the air in the reactor, the pressure was raised to 220 ° C, and the reaction was kept at a constant temperature for 2.5 hours, and then the heating was stopped and the temperature was slowly lowered to form a reaction solution. The reaction solution was precipitated by adding water, and the solid was collected by filtration. The solid was then washed with ethanol and 5 wt% potassium hydroxide solution, water and methanol, respectively, and vacuum dried to obtain the polymer resin P3.
[0088] Example 4
[0089] The structural formula of the polymer resin P4 in this embodiment is: Where n is 30.
[0090] Please refer to Figure 2 and Figure 4 The preparation method of the polymer resin P4 in which R is a hydroxyl group is as follows:
[0091] 70 mL of NMP and 3.77 g of sodium sulfide were added to the autoclave from the feed port. The temperature was raised to 140 ° C, dehydrated for half an hour, and 0.5 g of lithium chloride and sodium carbonate were added, and about 8.695 g of 2,4-dichloro-6-methoxy-1,3,5-triazine was added, with the molar ratio of sodium sulfide to 2,4-dichloro-6-methoxy-1,3,5-triazine being 1:1. The reactor was sealed, and after nitrogen replaced the air in the reactor, the pressure was raised to 220 ° C, and the reaction was kept at a constant temperature for 2.5 hours, and then the heating was stopped and the temperature was slowly lowered to form a reaction solution. The reaction solution was precipitated by adding water, and the solid was collected by filtration. The solid was then washed with ethanol and 5 wt% potassium hydroxide solution, water and methanol, respectively, and vacuum dried to obtain the polymer resin P2.
[0092] Take polymer resin P2 as the reactant and fully dissolve it in 30 times the volume of dichloromethane under argon atmosphere. Cool the solution to 0°C, add 1M BBr3 solution in dichloromethane, the molar ratio of boron tribromide to polymer resin P2 is 3:1, stir at 0°C for 30 minutes and stir at room temperature for 20 hours. After water quenching, dichloromethane is removed by rotary evaporator. The reaction solution is diluted with methanol, then precipitated with water, and the methanol dispersion and water precipitation process are repeated three times. Filter and collect the precipitate, wash with water, and vacuum dry to obtain polymer resin P4.
[0093] Comparative Example
[0094] The commercially available polycarbonate resin material A1, the isocyanate-thiol cured resin material A2, and the hydroxyl-modified polyphenylene sulfide resin material A3.
[0095] Test example
[0096] The polymer resins P1 to P4 prepared in the above-mentioned Examples 1 to 4 and the resin materials A1, A2, A3 of the comparative examples were subjected to the following tests.
[0097] 1. Refractive index test. The purified polymer resins P1 to P4 are dispersed in a polar solvent, such as tetrachloroethane, and then spin-coated on a silicon wafer by spin coating. After baking, the refractive index is tested using an ellipsometer. The refractive indexes of the polymer resins P1 to P4 prepared in Examples 1 to 4 are shown in Table 1.
[0098] 2. Abbe number test. The Abbe number is calculated by the refractive index at wavelengths of 486.nm, 587.6nm and 656.3nm. The calculation formula is as follows:
[0099] Vd=(n D -1) / (n F -n C )
[0100] The Abbe numbers of the polymer resins P1 to P4 prepared in Examples 1 to 4 obtained through testing are shown in Table 1.
[0101] 3. Water absorption test. The polymer resin prepared in each example was injected to obtain a 2 mm thick plate-shaped molded sheet, and the water absorption after immersion at 23°C for 24 hours was measured according to ISO62. The water absorption of the polymer resin prepared in Examples 1 to 4 is shown in Table 1.
[0102] 4. Light transmittance test. The purified polymer resin is dispersed in a polar solvent, such as tetrachloroethane, and then spin-coated on the surface of a glass substrate by a spin coating method. After baking, a haze meter is used to test. Among them, the light transmittances of the polymer resins P1 to P4 prepared in Examples 1 to 4 are shown in Table 1 after testing.
[0103] 5. Glass transition temperature (Tg) test. The test was conducted using a 2910 differential scanning calorimeter manufactured by TA Instruments Japan at a heating rate of 10°C / min. The glass transition temperatures (Tg) of the polymer resins P1 to P4 prepared in Examples 1 to 4 are shown in Table 1.
[0104] 6. UV aging test: UV aging test box (light source power 650mw, irradiation 4h, stop 4h as one cycle, a total of 24 cycles).
[0105] Table 1 Performance test of polymer resins P1 to P4 in Examples 1 to 4 and comparative resin materials A1 to A3
[0106]
[0107] As can be seen from Table 1, the polymer resins P1 to P4 prepared in Examples 1 to 4 of the present invention all have high refractive index (refractive index greater than 1.78), which is much higher than the polycarbonate resin material A1 and the resin material A2 formed by curing of isocyanate-thiol in the comparative example.
[0108] The Abbe number of each polymer resin of the present invention is less than 30 and greater than 20, indicating that the polymer resins P1 to P4 have no obvious dispersion, clear vision, and are comfortable to wear as materials for glasses.
[0109] The water absorption rate of each polymer resin of the present invention is less than 0.15%, indicating that the polymer resins P1 to P4 have lower water absorption rates and excellent waterproof properties.
[0110] The light transmittance of each polymer resin of the present invention is greater than 80%, indicating that the polymer resins P1 to P4 have good light transmittance and good light efficiency.
[0111] The Tg of each polymer resin of the present invention is greater than 140°C, so the polymer resins P1 to P4 have a higher glass transition temperature, indicating good heat resistance, oxidation resistance and stability, which are much higher than the resin material A1 and resin material A2 in the comparative example. Although the Tg of the hydroxyl-modified polyphenylene sulfide resin material A3 is higher, it is more brittle.
[0112] The yellowness change of the polymer resins P1 to P4 after aging of the present invention is much smaller than that of the resin material A1 and the hydroxyl-modified polyphenylene sulfide resin material A3 in the comparative example, indicating that the polymer resin of the present invention has excellent anti-yellowing performance.
[0113] In summary, the polymer resin of the present invention has a high refractive index (its refractive index is greater than 1.8), a high light transmittance (the light transmittance is greater than 80%), excellent waterproof performance, no obvious dispersion and can ensure clear vision, good heat resistance, excellent antioxidant property, good stability, and excellent anti-yellowing performance.
[0114] The catalyst, auxiliary agent, reaction temperature, reaction time and polymerization degree n selected in Examples 1 to 4 of the present invention are exemplary and should not be construed as limiting the scope of protection of the present invention. It can be understood by those skilled in the art that the catalyst in the above embodiments can also be any one of aluminum chloride, magnesium chloride, lithium acetate, lithium benzoate, lithium stearate and caprolactam, or can be a combination of multiple of lithium chloride, aluminum chloride, magnesium chloride, lithium acetate, lithium benzoate, lithium stearate and caprolactam; the auxiliary agent in the above embodiments can also be any one of sodium hydroxide, benzoate and phosphate, or can be a combination of multiple of sodium carbonate, sodium hydroxide, benzoate and phosphate. The temperature in the above embodiments can also be other temperatures between 200°C and 270°C; the above reaction time can also be other reaction times between 2h and 6h. n in the above embodiments can also be any optional value between 1 and 10000, which is not specifically limited here and should be included in the scope of protection of the present invention.
[0115] The terms "first" and "second" in the present invention are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0116] In the description of the present application, “plurality” means two or more than two, unless otherwise clearly and specifically defined.
[0117] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A polymer resin, characterized in that It has the following general structural formula as shown in Formula I: Wherein, the value of n is a positive integer between 1 and 10000; and R is an electron-rich group.
2. The polymer resin according to claim 1, characterized in that R is selected from any one of hydroxyl, amino, methoxy and phenyl; and / or, The polymer resin is selected from the group consisting of Any one of the compounds in .
3. The polymer resin according to claim 1 or 2, characterized in that The refractive index of the polymer resin is higher than 1.
8.
4. A method for preparing a polymer resin as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: Using sodium sulfide with a molar ratio of 1:1 and a structural formula of The dichlorotriazine compound is used as a reactant, and is subjected to a constant temperature catalytic reaction with a solvent N-methylpyrrolidone for a period of time, and the product is cooled and cleaned to obtain a general formula of of polymer resin.
5. The method for preparing a polymer resin according to claim 4, characterized in that: The temperature of the isothermal reaction is 200°C to 270°C; the time of the isothermal reaction is 2h to 6h; and / or, The catalyst used in the reaction includes at least one of lithium chloride, aluminum chloride, magnesium chloride, lithium acetate, lithium benzoate, lithium stearate and caprolactam; and / or, The auxiliary agent used in the reaction includes at least one of sodium carbonate, sodium hydroxide, benzoate and phosphate; The sodium sulfide and the dichlorotriazine compound are protected by a nitrogen atmosphere during the reaction; and / or, The washing liquid used during cleaning is one or more of ethanol, potassium hydroxide solution, water and methanol.
6. The method for preparing a polymer resin according to claim 4 or 5, characterized in that: The dichlorotriazine compound is one of 4,6-dichloro-1,3,5-triazine-2-amine, 2,4-dichloro-6-methoxy-1,3,5-triazine, and 2,4-dichloro-6-phenyl-1,3,5-triazine; When 4,6-dichloro-1,3,5-triazine-2-amine is used as the reactant, the final structure is Polymer resin; When 2,4-dichloro-6-methoxy-1,3,5-triazine is used as the reactant, the final structure is Polymer resin; When 2,4-dichloro-6-phenyl-1,3,5-triazine is used as the reactant, the final structure is of polymer resin.
7. The method for preparing a polymer resin according to claim 6, characterized in that: The following steps are also included: The structural formula is The polymer resin is used as a reactant, dissolved in dichloromethane under an argon atmosphere, and a boron tribromide solution is added, stirred at 0°C for a first time, stirred at room temperature for a second time, and the dichloromethane is removed to leave the reaction solution. The reaction solution is dispersed with methanol and precipitated with water multiple times to obtain a precipitate with the structural formula: of polymer resin.
8. The method for preparing a polymer resin according to claim 7, characterized in that: The first time is 20 minutes to 40 minutes, and the second time is 10 hours to 30 hours.
9. An optical waveguide structure, characterized in that: A substrate comprising a polymer resin as claimed in any one of claims 1 to 3; or a high-folding film material made of a polymer resin as claimed in any one of claims 1 to 3.
10. An optical device, characterized in that: include: The optical waveguide structure as claimed in claim 9.